Inkjet‐Printed PEDOT:PSS Electrodes on Paper for Electrocardiography. Issue 6 (25th January 2017) - Bihar, Eloïse; Roberts, Timothée; Saadaoui, Mohamed; Hervé, Thierry; De Graaf, Jozina B.; Malliaras, George G.
Abstract : Inkjet‐printed PEDOT:PSS electrodes are shown to record cutaneous electrophysiological signals such as electrocardiograms via a simple finger‐to‐electrode contact. The recordings are of high quality and show no deterioration over a 3 month period, paving the way for the development of the next generation of low‐cost, convenient‐to‐use healthcare monitoring devices.